2021
DOI: 10.3389/fchem.2021.711488
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Photodetectors Based on Chiral Materials: A Review

Abstract: Circularly polarized light (CPL) plays an important role in many photonic techniques, including tomographic scanning based on circular polarization ellipsometry, optical communication and information of spin, and quantum-based optical calculation and information processing. To fully exploit the functions of CPL in these fields, integrated photoelectric sensors capable of detecting CPL are essential. Photodetectors based on chiral materials can directly detect CPL due to their intrinsic optical activity, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 109 publications
(163 reference statements)
0
54
0
1
Order By: Relevance
“…However, such bulky and complicated optical systems by using free-space polarizer have intrinsic drawbacks such as limited speed, limited accuracy, and incomplete polarization state detection 9 . Recent advances in low-dimensional nanophotonic technologies have unveiled fascinating approaches to develop the next-generation polarimeters 10 , 11 . As a potential candidate for the next-generation compact polarimeters, on-chip polarization-sensitive photodetectors have been widely studied recently owing to their advantages including high level of miniaturization and ultrahigh-density integration.…”
Section: Introductionmentioning
confidence: 99%
“…However, such bulky and complicated optical systems by using free-space polarizer have intrinsic drawbacks such as limited speed, limited accuracy, and incomplete polarization state detection 9 . Recent advances in low-dimensional nanophotonic technologies have unveiled fascinating approaches to develop the next-generation polarimeters 10 , 11 . As a potential candidate for the next-generation compact polarimeters, on-chip polarization-sensitive photodetectors have been widely studied recently owing to their advantages including high level of miniaturization and ultrahigh-density integration.…”
Section: Introductionmentioning
confidence: 99%
“…[83] Later on, similar approaches were reconfirmed by Bajpai et al, and they found that the device performance could be further improved by optimizing the layer thickness and alkyl chain length of discotic liquid crystal. [84] Considering the unique macroscopic helicoidal structure and the tunable helix pitch of cholesteric liquid crystals, they are extensively applied in reflectors, [85] optical polarizers, [86] shutters, [87] and laser applications. [88] With regard to organic solar cells, cholesteric liquid crystals were developed as an additive in bulk heterojunction layer to improve the performance of organic solar cells.…”
Section: Nonvolatile Memory Applicationsmentioning
confidence: 99%
“…Considering the unique macroscopic helicoidal structure and the tunable helix pitch of cholesteric liquid crystals, they are extensively applied in reflectors, [ 85 ] optical polarizers, [ 86 ] shutters, [ 87 ] and laser applications. [ 88 ] With regard to organic solar cells, cholesteric liquid crystals were developed as an additive in bulk heterojunction layer to improve the performance of organic solar cells.…”
Section: Organic Photovoltaics Applicationsmentioning
confidence: 99%
“…A concept that recently gained momentum in the metal halide perovskite literature is the use of chiral ammonium cations in order to induce novel functionality in HMHs. 5,[15][16][17][18][19][20] The successful transfer of chirality from the cation to the HMH as a whole would yield a material that combines the favorable electronic properties of the inorganic material with the chirality of the organic compound, rendering chiral HMHs an exceptionally attractive candidate for the generation and detection of circularly polarized light.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…Several chiral organic materials, such as small molecules and conjugated polymers, have been demonstrated to efficiently differentiate between left-and right-handed circularly polarized light in photodetectors. 5 Instead, in inorganic materials, circularly polarized emission only occurs when the symmetry of the system is lowered by…”
Section: Introductionmentioning
confidence: 99%